Making Sense – With Ruth Manorama, A Dalit Feminist Activist. Issue 1 (June 2016) - Pathak, Dev N.
The idea of Dalit summons critical revisiting in the contemporary political milieu in India. This could be a hermeneutically creative response to the onslaughts (by old as well as new worshippers of the iconic idols) on Dalits, their ideologies, epistemologies, politics and culture. To enhance the scope of Dalit politics it is imperative to make it more inclusive without compromising on the fundamental commitments. The conversation with one of the renowned Dalit-feminist activists Ruth Manorama is a pertinent occasion for raising some of the difficult questions related to Dalit thoughts and praxis, the status of Dalit women, the need to revisit Ambedkarite radicalism, and the possibility of the Dalit culture of resistance and progress. This conversation is, however, not aimed at a conclusive understanding. It seeks to spill the beans, ferret out bone(s) of contention and spread the seeds of thought (epistemes) for gradual germination. In a nutshell, the conversation is reflective of the intersections of the academic interests of Dev Pathak and an activist's interests of Ruth Manorama. The intersection, divergent and harmonious, is a testimonial for the validity of the conversation.